Pulmonary Aspergillosis due to Aspergillus flavus Infection in a Captive Eclectus Parrot (Eclectus roratus) - Churria, Carlos D. Gornatti; Reynaldi, Francisco J.; Origlia, Javier A.; Marcantoni, Hugo A.; Píscopo, Miguel V.; Loyola, Miguel A. Herrero; Reinoso, Enso H.; Petruccelli, Miguel A. (Brazilian Journal of Veterinary Pathology, 2012)
A 2-year-old captive, male Eclectus parrot (Eclectus roratus), with a previous history of neurologic signs episodes, was found dead in its cage without premonitory signs in a private aviary. At necropsy, yellow and caseous nodules were observed in the lungs. Microscopically, the nodules were composed of granulomas that had a necrotic center with intralesional hyphae typical of Aspergillus spp. and a peripheral inflammatory cell response composed of macrophages and multinucleated giant cells. The mycologic culture allowed the isolation and identification of A. flavus from lung samples. The gross and microscopic lesions, in combination with the mycologic identification provided the diagnosis of pulmonary aspergillosis due to A. flavus infection. To the authors´ knowledge, this is the first report of mycotic pneumonia caused by A. flavus infection in Psittaciformes.